2018 Days on Diffraction (DD) 2018
DOI: 10.1109/dd.2018.8553047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the currents in the Dirichlet and Neumann shortwave diffraction problems of a plane wave from smooth prolate bodies of revolution

Abstract: This paper continues the series of works [1-5] on the shortwave diffraction on the prolate body of revolution. The numerical comparison of the wave currents for Dirichlet and Neumann boundary conditions confirms the continuous transition of the current from the lit area into the shadowed zones through Fock's zone. The formulae for the currents were obtained according to the Leontovich-Fock parabolic equation method [6]. We investigated the influence of the correction term that contains the large parameter, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A. S. Kirpichnikova and N. Ya. Kirpichnikova obtained the first three terms of the wave field approximation for the problem with Neumann boundary conditions [7,8]. The novelty of the present paper is in the description of the creeping waves in the shadow region for the Neumann problem.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…A. S. Kirpichnikova and N. Ya. Kirpichnikova obtained the first three terms of the wave field approximation for the problem with Neumann boundary conditions [7,8]. The novelty of the present paper is in the description of the creeping waves in the shadow region for the Neumann problem.…”
Section: Introductionmentioning
confidence: 90%
“…This two-scale expansion allows us to obtain formulae for calculating the wave field, in particular, the current on the surface of the scatter at different ratios between M (s) and Λ(s). It can be shown that the recurrent system of equations (8) will retain its asymptotic character at M (s) provided that Λ(s) = M 2−ε for 0 < ε < 2. We use the following scheme to solve system (8).…”
Section: Problem Statement and Analysismentioning
confidence: 99%
See 1 more Smart Citation